A Study on Relationship of Sustainable Development Goals with the Usage of Cosmetic Skin Care Products- A Study - Ms. B. Harini; Dr. N. Rajamannar (Recent Trends in Cosmetics, 2025)
Sustainable Development Goals is nothing but making addressing the conflicts worldwide and giving better lives for people in the globe. The main aim is to tackle the challenges along with others to make the globe more sustainable for future generations. There are seventeen goals defined in SDGs which are focused on sustainable development. They are exclusively designed for eradication of poverty, protection of the environment, and the promotion of our well-being.In the context of the beauty and personal care industry, cosmetic skincare products play a significant role in influencing several of these goals. Positively, the industry supports economic growth by creating jobs and encouraging innovation through research and development of new formulations. Companies adopting eco-friendly packaging and sustainable sourcing practices contribute to responsible consumption and production and climate action . Moreover, initiatives promoting gender equality are often supported by empowering women in the workforce and encouraging body positivity.However, there are also negative impacts. The overuse of plastics in packaging and harmful chemicals in products contribute to environmental degradation, affecting life below water and life on land . Unethical labor practices and greenwashing are also concerns that undermine progress toward the SDGs.Thus, while the skincare industry has the potential to align with the SDGs, responsible practices and greater awareness are essential to maximize its positive impact and reduce harm.Sustainable Development Goals is nothing but making addressing the conflicts worldwide and giving better lives for people in the globe.
Keywords: Cosmetic Skincare Industry; Environmental impact; Ethical Sourcing; Responsible Consumption; sustainable development goals (SDGs)